Vessel - Lee, Jon En (Nanyang Technological University, 2020)
Vessel is a sleeping implement designed as an object of meditation. Its purpose to focus the user’s consciousness onto their immediate reality and increase involvement through its austere design and changeable forms to correspond to the user’s stages in life. In contrast to most products whose functions centre around comfort and convenience, it requires maintenance and provides a basic usage without much in the way of comfort. This changes its usage, which in other products is a usually unconscious process, into one of mindfulness and awareness.